STUDENTS’ ERROR ANALYSIS USING PERFECT TENSE - ST Marhana Rullu; Marto Marto (BABASAL English Education Journal, 2021)
The purpose of this research is to analysis what kinds error in perfect tense made by student in English education study program and to find out the cause of error made by students at English education study program in Muhammadiyah Luwuk University. The method of this research is qualitative-descriptive. This research used two instruments, the first instrument is test and the second instrument is interview. This research used data analysis technique by Miles and Huberman stated that data analysis technique into three parts, those are data reduction, data display and conclusion drawing. The research subject is students in English education study program that already programed the general English structure. The result of the test found four types of error. Those are addition, omission, substitution and miss ordering. And the result of the interview found four causes of error. Those are interlingua transfer, intralingua transfer, context of learning and communication. The highest error is substitution with 110 error. and the most cause of error that happened in students English education study program is intralingua transfer.